Sustainable Development of a Dairy and Grocery Subcomplex in Novosibirsk Region - Shelkovnikov, Sergey A.; Tsoy, Sergey A.; Samokhvalova, Anastasiia A.; Petukhova, Marina S.; Fedorov, Michail N. (International Review of Management and Marketing, 2016)
The research reviews the promising directions of sustainable development of a dairy and grocery subcomplex of agribusiness in the region. As a result of the analysis and generalization of theoretical research by the scientists, the theoretical basis for sustainable development of a dairy and grocery subcomplex of the region was refined, which is considered in the context of the processes of globalization and integration of the Russian economy into the world space in terms of labor productivity growth. The methods of calculation of parameters of milk production in the region were developed, taking into account the growth of labor productivity, as well as the mechanism of distribution of profits from the sale of dairy products. The proposed distribution mechanism will allow to raise additional funds in the field of milk production, which currently does not participate in the distribution of profits from milk processing and sale of dairy products. Proposals on updating the departmental target program "Development of dairy cattle breeding in Novosibirsk region for 2014-2020" were submitted in order to ensure the necessary funding for the modernization of livestock farms and their equipment with modern machinery. The introduction of advanced technology and equipment will allow increasing milk production, improving its quality, and reducing the influence of the human factor due to growth in labor productivity. A milk production forecast through to 2020 in Novosibirsk region was developed. Keywords: dairy industry, milk production, labor productivity, distribution of profits, government support. JEL Classifications: M11; O13; Q10; Q12; Q19